(untitled) (Baghdad Science Journal, 2004)
Different coating layers of fluorescent agent (FCA) on the solar cells were used. An increase of 35% in the energy conversion efficiency of the solar cell have been obtained. This increase is attributed to the reduction ofthe reflected light, eflection spectra show low values at higher thickness which explained the increase ofthe conversion efficiency with increases of layer thickness.